Stachytarpheta jamaicensis Blue Porterweed - Edward Gilman (EDIS)
This document provides an in-depth look at Stachytarpheta jamaicensis, commonly known as Blue Porterweed. It describes the plant’s characteristics, including its growth habits, appearance, and flowering patterns. The document highlights the plant’s uses in landscaping, such as hedges, borders, and mass plantings, and its ability to attract butterflies. Additionally, it covers the plant’s preferred growing conditions, including light, soil, and water requirements, as well as its high drought tolerance and minimal pest issues. Original publication date October 1999.